Impaired pulmonary function increases the risk of gout: evidence from a large cohort study in the UK Biobank - Zijian Kang; Jianzheng Zhang; Chen Zhu; Ying Zhu; Hanlei Jiang; Qiang Tong; Sheng-Ming Dai (BMC Medicine)
Abstract Background Pulmonary function is increasingly recognized as a key factor in metabolic diseases. However, its link to gout risk remains unclear. The study aimed to investigate the relationship between pulmonary function and the risk of developing gout and the underlying biological mechanisms. Methods Our study included 420,002 participants with complete pulmonary function data from the UK Biobank. Logistic regression was used to evaluate gout prevalence among individuals with different pulmonary function statuses. Propensity score matching (PSM) created balanced groups, while Cox regression gauged the risk association between reduced lung capacity and gout compared with normal function. Mendelian randomization (MR) analysis was used to verify causal associations. Non-linear correlations were assessed with restricted cubic spline (RCS) analysis, and mediation analysis was used to explore the role of blood biomarkers. Mediation analyses were used to investigate the potential mediating role of biomarkers in the association. Results Cross-sectional analysis revealed a higher prevalence of gout in individuals with preserved ratio of impaired spirometry (PRISm) of 6.31% and chronic obstructive pulmonary disease (COPD) of 6.26% than in those with normal pulmonary function (3.45%). After adjustment for covariates, both PRISm (odds ratio [OR] 1.24, 95% confidence interval [CI] 1.17–1.31) and COPD (OR 1.14, 95% CI 1.07–1.22) were significantly associated with gout. Longitudinal analysis confirmed that impaired pulmonary function significantly increased the risk of developing gout (hazard ratio [HR] 1.32, 95% CI 1.24–1.40). MR further revealed a potential causal effect of decreased pulmonary function on an increased risk of gout. Subgroup analysis revealed significant interactions between impaired pulmonary function and several factors, including body mass index (BMI), levels of physical activity, and diabetes status, in their associations with the risk of gout. RCS analysis showed a nonlinear relationship between pulmonary function indicators and gout incidence, characterized by an inverse S-shaped curve. Mediation analysis revealed that urate levels (49.1% mediation proportion), C-reactive protein (CRP) levels (6.62%), monocyte counts (1.33%), and neutrophil counts (4.85%) significantly mediated the relationship between pulmonary function and the risk of gout. Conclusions Our study revealed a significant association between impaired pulmonary function and an increased risk of developing gout. The association might be partially mediated by biomarkers including urate levels, inflammatory markers, and immune cell counts.